2015 IEEE International Symposium on Power Line Communications and Its Applications (ISPLC) 2015
DOI: 10.1109/isplc.2015.7147614
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-hidden Markov modeling of a low complexity FSK-OOK in-house PLC and VLC integration

Abstract: The integration of power line communication (PLC) and visible light communication (VLC) is increasingly receiving a lot of research interest with the advent of (IEEE 1901, ITUT G.9960/61) and IEEE 802.15.7 standards for PLC and VLC respectively. In particular, there is an underlying gain that could be achieved by leveraging the existing ubiquitous power line network infrastructure to render connectivity, while we also exploit the illumination system of power-saving Light Emitting Diodes (LEDs) for wireless d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…This impulsive noise may cause either bit or burst errors in data transmission power line [6,13,14]. When it comes to narrowband noise, it can be modeled as the output of the bandpass filter driven by the AWGN in the discrete sampling space, which can can also be represented as a low frequency sinusoid [9,12,13], (3) where is the carrier frequency of the interferer, and nnb based on prior research has been found to reach power levels of 30 dB greater than the background noise at frequencies greater than 1 MHz .…”
Section: Channel Noise Effect On Plc Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…This impulsive noise may cause either bit or burst errors in data transmission power line [6,13,14]. When it comes to narrowband noise, it can be modeled as the output of the bandpass filter driven by the AWGN in the discrete sampling space, which can can also be represented as a low frequency sinusoid [9,12,13], (3) where is the carrier frequency of the interferer, and nnb based on prior research has been found to reach power levels of 30 dB greater than the background noise at frequencies greater than 1 MHz .…”
Section: Channel Noise Effect On Plc Systemmentioning
confidence: 99%
“…In order to make the Power Line Communication (PLC) based networks more practical by having mobility at the last inch connectivity the VLC can be utilised. The ubiquitous nature and advantages for which these two medium of communication possess can be harnessed, such that VLC is made to offer a good complementary wireless data communication to the existing ubiquitous InHouse PLC channel [12]. The idea of integrating both systems was pioneered by Komine et.al in 2002 [9], which has now been taken advantage of in various applications [1,2].…”
Section: Integration Of Plc and Vlcmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its first presentation by Komine and Nakagawa [1], some research focus areas reported in literature regarding the HPV system include, PLC/VLC integration techniques [6]- [8], channel modelling [4], [9], modulation, multi-carrier and multi-user techniques [10]- [14], for achieving a reliable, spectral and energy efficient HPV system.…”
Section: Introductionmentioning
confidence: 99%